Konservasi Burung Endemik Nuri Talaud melalui Pendekatan Partisipatif Masyarakat Lokal - Sari, Nindya Duta; Relatami, A. N. R.; Karim, Qadri; Ramadhani, Shafira Zulfa; Firman, Sri Wahyuni; Kasim, Muh (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Talaud Parrot (Eos histrio), locally known as “Sampiri,” is an endemic species of the Talaud Islands that is currently endangered due to illegal capture and habitat loss. This conservation program aims to preserve the Talaud Parrot population through a participatory approach involving local communities. The methods applied include population monitoring and conservation outreach, training in integrated organic farming using permaculture methods as an alternative livelihood, as well as rehabilitation and release of rescued birds at the Tasikoki Wildlife Rescue Center. Educational activities were carried out through school-based awareness programs and eco-camp events to instill conservation awareness from an early age. The results of the program showed increased community understanding and participation in the conservation of endemic birds, reduced hunting activities, and the establishment of an organic farmers’ group in Dapalan Village as a form of environmentally friendly economic empowerment. The program also strengthened synergy among institutions—Pertamina, the Masarang Foundation, the North Sulawesi BKSDA, and local communities—as a model of multi-stakeholder partnership in community-based conservation. The ecological, social, and economic impacts demonstrate that participatory conservation efforts are effective in reducing illegal wildlife trade and improving community welfare. Overall, this program serves as a tangible example of sustainable collaboration to protect the biodiversity and ecological identity of the Talaud Islands.